Impact of brand hate on consumer well-being for technology products through the lens of stimulus organism response approach - Attiq, Saman; Hamid, Abu Bakar Abdul; Shah, Hassan Jalil; Khokhar, Munnawar Naz; Shahzad, Amna (Frontiers in Psychology, 2022)
Consumer wellbeing is a micromarketing concept which emphasizes on contributions of marketing activities in social welfare. The major objective of the current study is to analyze the impact of self-incongruence on brand dissatisfaction, brand hate and consumer wellbeing. This study has utilized Self-incongruity Theory and Stimulus-Organism-Response model to test the impact of self-incongruity on anti-consumption and consumer voice behaviors and subsequent effects on consumer wellbeing. Data was collected from young consumers of technology products from major cities of Pakistan. 592 consumers participated in paper and pencil questionnaire using purposive sampling technique. Data has been analysed using partial least square structural equation modelling. Findings of this study reveal that functional and symbolic incongruity predict brand hate and dissatisfaction, which is positively related to brand retaliation. Brand retaliation is negatively related to consumer wellbeing. This study offers implications for product designers, marketers, advertisers and other stakeholders to improve congruence between what young consumers of technology products expect and what brands are offering to mitigate negative attitudes and behaviors and increase consumer wellbeing.